Development of a standardised training curriculum for robotic surgery: a consensus statement from an international multidisciplinary group of experts - Ahmed, Kamran; Michel, Maurice Stephan (BJU international, 2015)
Objectives: To explore the views of experts about the development and validation of a robotic surgery training curriculum, and how this should be implemented. Materials and methods: An international expert panel was invited to a structured session for discussion. The study was of a mixed design, including qualitative and quantitative components based on focus group interviews during the European Association of Urology (EAU) Robotic Urology Section (ERUS) (2012), EAU (2013) and ERUS (2013) meetings. After introduction to the aims, principles and current status of the curriculum development, group responses were elicited. After content analysis of recorded interviews generated themes were discussed at the second meeting, where consensus was achieved on each theme. This discussion also underwent content analysis, and was used to draft a curriculum proposal. At the third meeting, a quantitative questionnaire about this curriculum was disseminated to attendees to assess the level of agreement with the key points. Results: In all, 150 min (19 pages) of the focus group discussion was transcribed (21 316 words). Themes were agreed by two raters (median agreement κ 0.89) and they included: need for a training curriculum (inter-rater agreement κ 0.85); identification of learning needs (κ 0.83); development of the curriculum contents (κ 0.81); an overview of available curricula (κ 0.79); settings for robotic surgery training ((κ 0.89); assessment and training of trainers (κ 0.92); requirements for certification and patient safety (κ 0.83); and need for a universally standardised curriculum (κ 0.78). A training curriculum was proposed based on the above discussions Conclusion: This group proposes a multi-step curriculum for robotic training. Studies are in process to validate the effectiveness of the curriculum and to assess transfer of skills to the operating room.